Assessing The Protection Of Women's Rights In The Perspective Of Feminism During The Covid-19 Pandemic - Yoel, Siciliya Mardian (JURNAL LEGALITAS, 2021)
Abstract This study aims to identify the laws and regulations that regulate women's human rights and analyze them using them to determine the effectiveness of these laws and regulations in protecting women's human rights during the pandemic. The research was conducted using normative legal research methods using a conceptual approach and a statutory approach. The collection of legal materials is carried out using a literature study and the legal materials will be analyzed using Feminist Legal Theory. The results of the study show that there are several women's human rights that have been regulated in Indonesian laws and regulations, including: (1) The right to be free from gender discrimination (UU HAM); (2) The right to justice and gender equality (UU HAM, UU PKDRT); (3) The right to get protection as a victim (UU PKDRT); (4) The right to recognition and respect for human rights in all matters relating to citizens (UU Kewarganegaraan); (5) The right to be free from racial discrimination (UU PTPPO); (6) Political Rights (UU Parpol, UU Pemilu); and (7) The right to be free from discriminatory treatment against a social group that is still underdeveloped (UU Parpol, UU Pemilu). With regard to these laws and regulations, by focusing only on aspects of legal protection, namely protection against violence (both physical and sexual) against women, it shows that the existing legal umbrella is not effective enough to protect women. This is because the existence of laws and regulations alone cannot guarantee the implementation of women's human rights. Legislation must be followed by gender-sensitive law enforcement and no less important is a cultural change in society.